Anti-doping sciences, abjection and women’s sport as a protected category - Schneider, Angela J.; Oldham, Alan C.; Butcher, Loughran H. G. (Frontiers in Sports and Active Living, 2023)
In this article we explore the relationships amongst anti-doping sciences, ‘abjection,’ and the protection of ‘women's’ sport. We introduce three novel concepts: ‘abjection bias,’ ‘abjection potential,’ and ‘intersectional abjection,’ as tools with the potential to provide greater nuance to understanding the context for these contentious issues in contemporary sport. The debate concerning participation in women's sport—especially elite sport—of people who do not fit within traditional definition of ‘women’ is increasingly fraught with acrimony with anti-doping sciences often recruited as arbitrator. With access to opportunities such as participation at the Olympic Games at stake, emotions run high in arguments that typically centre on inclusion of transgender and gender diverse (TGD) athletes on the one hand and protection of the women's category on the other. While sport theorists have begun the important work of identifying the roots of these problems deep within the structure of modern sport and society itself, they have hitherto paid little attention to the philosophical underpinnings of that structure. Through the lens of feminist critical analysis, we seek, in this paper, to understand the complex role of ‘abjection’ in framing the current debate in sport and in related anti-doping sciences. From a clear definition of abjection as a perceived existential threat due to violation of the status quo, we introduce the new concepts of ‘abjection bias,’ ‘abjection potential,’ and ‘intersectional abjection’ in order to understand and explain what in common parlance we might call ‘gut reaction.’ By looking at the few notable previous treatments of sport abjection and highlighting the historical connections between anti-doping sciences and efforts to protect the women's category, we demonstrate that this co-development is, in part, more easily understood in the context of ‘abjection.’ We conclude that the clarity gained can also help to shed light on current policy decision-making in relation to the question of protecting the women's sport category.